Centralization versus Delegation in an Experimental Capital Budgeting Setting - Markus C. Arnold; Robert M. Gillenkirch (BuR - Business Research, 2011)
In an experiment, we model two stylized facts about capital budgeting practice, budgetary slack creation and delegation of decision-making authority. In our setting, under centralization, headquarters announces a budget, the division manager gives a cost report, and headquarters decides on the project. Under delegation, headquarters allocates a budget to the manager, and the manager is authorized to make the investment decision. We argue that the ability of headquarters to commit to a budget moderates the effect of delegation, and we find evidence in favor of our argument as there is an interaction effect of delegation and commitment to budgets. The effects of delegation are particularly strong when budgets are non-binding as delegation serves as a substitute for commitment in this case. This leads to smaller expenditures and to a higher headquarters payoff under delegation than under centralization. In contrast, when headquarters can commit to the budget, the descriptive data are consistent with our conjectures about the effects of honesty preferences, but the effects are too small to be significant.
urn:nbn:de:0009-20-29754
Keywords: 650; behavioral accounting; capital budgeting; centralization; delegation; experimental economics; slack; Investitionsrechnung; Experimentelle Ökonomik; Bilanzielle Bewertung; Unternehmenszentrale; Controlling